The Phenylpropanoid Pathway and Lignin in Defense against Ganoderma boninense Colonized Root Tissues in Oil Palm (Elaeis guineensis Jacq.) - Govender, Nisha T.; Mahmood, Maziah; Seman, Idris A.; Wong, Mui-Yun (Frontiers in Plant Science, 2017)
Basal stem rot (BSR), caused by the basidiomycete fungus, Ganoderma boninense, is an economically devastating disease in Malaysia. Our study investigated the changes in lignin content and composition along with activity and expression of the phenylpropanoid pathway enzymes and genes in oil palm root tissues during G. boninense infection. We sampled control (non-inoculated) and infected (inoculated) seedlings at seven time points (1, 2, 3, 4, 8, 12 weeks post-inoculation (wpi)) in a randomized design. The expression profiles of phenylalanine ammonia lyase (PAL), cinnamyl alcohol dehydrogenase (CAD), and peroxidase (POD) genes were monitored at 1, 2, and 3 wpi using real-time quantitative polymerase chain reaction (qPCR). Seedlings at 4, 8, and 12 wpi were screened for lignin content, lignin composition, enzyme activities (PAL, CAD and POD), growth (weight and height), and disease severity (DS). Gene expression analysis demonstrated up-regulation of PAL, CAD, and POD genes in the infected seedlings, relative to the control seedlings at 1, 2, and 3 wpi. At 2 and 3 wpi, CAD showed highest transcript levels compared to PAL and POD. Disease severity increased progressively throughout sampling, with 5, 34, and 69% at 4, 8, and 12 wpi, respectively. Fresh weight and height of the infected seedlings were significantly lower compared to the control seedlings at 8 and 12 wpi. Lignin content of the infected seedlings at 4 wpi was significantly higher than the control seedlings, remained elicited with no change at 8 wpi, and then collapsed with a significant reduction at 12 wpi. The nitrobenzene oxidation products of oil palm root lignin yielded both syringyl and guaiacyl monomers. Accumulation of lignin in the infected seedlings was in parallel to increased syringyl monomers, at 4 wpi and 8 wpi. The activities of PAL and CAD enzymes in the infected seedlings at DS=5-34% were significantly higher than the control seedlings and thereafter collapsed at DS=69%.